DIGITAL MARKETING AND CUSTOMER EXPERIENCE IN IBADAN, OYO STATE - Abiola Abass Carim; Kayode Muhammed Ibrahim; Solomon Olugbade Adedokun (Malete Journal of Accounting and Finance)
With the increasing reliance on digital marketing, companies face challenges in adapting their strategies to effectively connect with consumers. As digital marketing reshapes consumer relationships, businesses must navigate the complexities of building trust, engagement, and loyalty in an increasingly digital landscape. This research aims to examine the influence of digital marketing and customer experience in the Ibadan metropolis of Oyo State. This study used a descriptive survey research design in which a structured questionnaire was used to elicit information from the target respondents, who were customers patronizing online businesses in Ibadan. A self-structured questionnaire was utilized and questionnaires were distributed online to respondents as it gives room for equal representation of respondents. The population is infinite, and Cochran's (1977) formula was used to calculate the sample size of 385. The hypothesis was tested using multinomial regression. Statistical Package for Social Science (SPSS) was used to analyze the data. The result indicated a positive significant relationship between digital marketing strategies and customer experience in Oyo State, Nigeria. Also, internet marketing has become a valuable and significant strategy for companies to promote, advertise, and interact with more customers in the state. The study recommended that organizations should invest in creating compelling content, targeting advertising, and providing excellent online customer service to engage with more customers.